2005
DOI: 10.1002/cvde.200506384
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of HfO2 Films by Liquid Injection MOCVD Using a New Monomeric Alkoxide Precursor, [Hf(dmop)4]

Abstract: from 350 C to 650 C. Analysis by X-ray diffraction (XRD) shows that the films are amorphous at deposition temperatures of 400 C and below. At substrate temperatures above 450 C, the films adopt a monoclinic (a-HfO 2 ) phase with a fiber texture dependent upon growth temperature. Analysis by Auger electron spectroscopy (AES) shows that the films are nonstoichiometric and contain residual carbon (2.1 ± 11.6 at.-%) and nitrogen (0.4 ± 1.9 at.-%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…This is comparable with other highk dielectric films reported previously. [38,43] The leakage current density for the film grown by ALD using [(MeCp) 2 HfMe(mmp)] was more than one magnitude higher than the other films investigated. This is thought to be due to its physical thickness (< 2 nm), which allows an additional direct tunneling component of leakage current.…”
Section: Electrical Characterization Of the Hfo 2 Filmsmentioning
confidence: 92%
“…This is comparable with other highk dielectric films reported previously. [38,43] The leakage current density for the film grown by ALD using [(MeCp) 2 HfMe(mmp)] was more than one magnitude higher than the other films investigated. This is thought to be due to its physical thickness (< 2 nm), which allows an additional direct tunneling component of leakage current.…”
Section: Electrical Characterization Of the Hfo 2 Filmsmentioning
confidence: 92%
“…[10] The success of oxazoline ligands as stabilizing agents in catalysis as well as our ongoing interest in rhenium-catalyzed epoxidations [11][12][13][14][15] prompted us to investigate a largely unexplored oxazoline ligand in oxidorhenium(V) chemistry. We were surprised to find that 2-(hydroxymethyl)-2-oxazoline and derivatives thereof have, in general, limited used incoordinationchemistry.Thus,with(4,5-dihydrooxazol-2-yl)-methanol only a few Cr III , [16] Ni II , [17,18] Zr IV [19] and Hf IV [20] [a] Institute of Chemistry, Karl-Franzens-University Graz, Schubertstrasse 1, 8010 Graz, Austria E-mail: nadia. 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Hf-O(dmop) r bonds are significantly shorter than the weaker 4 ], and has also been used successfully for the deposition of HfO 2 films by liquidinjection MOCVD. [56] The films were deposited in the temperature range 350-650°C. Auger electron spectroscopy (AES) showed that residual carbon (2.1-11.6 at.-%) and nitrogen (0.4-1.9 at.-%) were present in the films.…”
Section: Mocvd Of Zro 2 and Hfomentioning
confidence: 99%